A Caribbean Affair: The Liberalisation of the Slave Trade in the Spanish Caribbean, 1784-1791 - José Luis Belmonte Postigo (Culture & History Digital Journal, 2019)
The liberalisation of the slave trade in the Spanish Caribbean ended with a series of political measures which aimed to revitalise the practice of slavery in the region. After granting a series of monopoly contracts (asientos) to merchant houses based in other western European nations to supply slaves to Spanish America, the Spanish monarchy decided to liberalise import mechanisms. These reforms turned Cuba, especially Havana, into the most important slave trade hub within the Spanish Caribbean. Havana was connected with both Atlantic and inter-colonial trade networks, while other authorised ports imported slaves from other Caribbean territories; Spanish, British, Dutch, Danish and American traders all participated in this trade, and slave trafficking became the most profitable form of commerce in the region during this period.